Controlled growth of Cu2O nanoparticles bound to cotton fibres. (5th May 2016) - Errokh, A.; Ferraria, A.M.; Conceição, D.S.; Vieira Ferreira, L.F.; Botelho do Rego, A.M.; Rei Vilar, M.; Boufi, S.
Highlights: In situ generation of nanoparticles (NPs) of cuprous oxide (Cu2 O) onto cotton fibres was proposed. A controlled oxidation of the surface of the fibre was used to adsorb Cu 2+ precursor. The content of Cu2 O NPs was made possible via the control of the carboxyl content. The hybrid cotton–Cu2 O was shown to exhibit good antibacterial properties. Abstract: A green, safe and fast procedure is presented for in situ generation of nanoparticles (NPs) of cuprous oxide (Cu2 O) onto cotton fibres at room temperature using water as a solvent. The method is based on a mild surface oxidation of cellulose fibres to generate in a controlled way carboxylic groups acting as a binding site for the adsorption of Cu 2+ via electrostatic coordination. Then, the adsorbed Cu 2+ ions were readly converted into Cu2 O by dipping the treated cotton fibres into a aqueous solution of a reducing agent. Field-emission scanning electron microscopy (FE-SEM), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD), as well as UV–vis absorption and emission spectroscopic methods were used to analyse the size, morphology, chemical composition and the crystalline structure of the generated nanoparticles on the fabrics. The morphology of the ensuing Cu2 O nanoparticles was shown to be dependent on the reduycing agent used. Antibacterial properties of the modified fibres were also investigated.